2023
DOI: 10.5937/jomb0-37343
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and hematological findings and risk factors associated with kidney impairment in patients with COVID-19

Abstract: Background : COVID-19 is a new pandemic that has infected millions of people worldwide and caused a high rate of morbidity and mortality. COVID-19 may have a harmful effect on body organs especially, the kidneys. Aims: The main aim of our research is to study the association between the severity of COVID-19 disease and biochemical parameters related to kidney function and to investigate certain risk factors of COVID-19-associated kidney disease. Methods: A total of 174 individuals, 121 COVID-19 pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Urine casts are closely related to PRO. Recent research has shown that proteinuria can also reflect the severity of renal function impairment caused by Coronavirus Disease 2019 ( 20 ). In adults, proteinuria is considered the excretion of more than 150 mg of urinary PRO per day and is suggestive of renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Urine casts are closely related to PRO. Recent research has shown that proteinuria can also reflect the severity of renal function impairment caused by Coronavirus Disease 2019 ( 20 ). In adults, proteinuria is considered the excretion of more than 150 mg of urinary PRO per day and is suggestive of renal disease.…”
Section: Discussionmentioning
confidence: 99%